Pengaruh Internet Banking, Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Dan Ukuran Perusahaan Terhadap Profitabilitas (Studi Kasus Pada Perusahaan Bank Umum Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022) - Lambung, Jane Sintha; Ec Rapel; Asi, Oktobria Y.; Hendrayati, Sri Lestari; Angela, Leliana Maria; Octaviani, Theresia (Balance: Media Informasi Akuntansi dan Keuangan, 2025)
This study aims to determine the effect of internet banking, capital adequacy ratio, non-performing loans, and company size on profitability in Commercial Banks listed on the Indonesia Stock Exchange (IDX) in 2020-2022.This study uses a quantitative method for its approach. The type of data used in this study is secondary data obtained from the company's annual financial report presented on the Indonesia Stock Exchange website and the website of each company. The population in this study were 45 public banks listed on the Indonesia Stock Exchange in 2020. The sampling technique used was the purposive sampling method so that 43 banks were selected as samples in this study. The data obtained were analyzed using the SPSS version 26 application. The results of the study show that Internet banking and non-performing loans have a negative and significant effect on profitability. While the capital adequacy ratio and company size have a positive and significant effect on profitability.